A tensegrity-based morphing module for assembling various deployable structures. (July 2022) - Zhang, Li-Yuan; Zheng, Yang; Yin, Xu; Zhang, Shuai; Li, Hai-Quan; Xu, Guang-Kui
Highlights: A morphing module is constructed by a prismatic tensegrity and two end plates. Direct/inverse theoretical models are established and validated by experiments. Our module can exhibit a series of symmetrical and asymmetrical deployments. Our module is flexible for various deployable assemblies with abundant shapes. Abstract: Deployable structures have a wide range of applications in, for instance, soft robotics, bionic machinery, aviation equipment, and programmable metamaterials. Tensegrity, based on the equilibrium of axially stretched and compressed elements, can be an attractive candidate for designing deployable structures. However, existing tensegrity-based deployable structures mostly hold symmetrical deformation modes, which greatly limits their applicable scenarios. To this end, we here propose a tensegrity-based morphing module that can exhibit not only symmetrical configurations, but also a series of asymmetrical configurations. This module is composed by a prismatic tensegrity and two end plates, in which the tensegrity contributes to the deformability of the module and the plates allow the module rather flexible to construct various deployable structures with abundant configurations. Our theoretical and experimental results both confirm that the proposed module is capable of symmetrical/asymmetrical deployment through a variety of active actuations. Finally, several quasi-one-dimensional structures are assembled by a number of the morphing modules as examples, and their flexible deformability helps to broaden the application prospects of tensegrity-based deployable structures.